Clinical Maternal-Fetal Medicine - Winn, Hung N.; Chervenak, Frank A.; Romero, Roberto (Series In Maternal Fetal Medicine, 2012)
"This is a comprehensive, one-stop online book relating to all areas of pregnancy and birth. The second edition of this easily searchable guide is edited by eminent experts in the field and includes new contributions from international authors. It will be an ideal reference for Maternal-Fetal Specialists and Generalists wanting an authoritative answer on any point. Key features: •Grouped in to six topics (modules) for convenience •Electronic search facility across all chapters •Approximately 700,000 words of text, 7000 references, 300 figures (including 100 in full colour), and 200 tables available to search Key topics: •All common pregnancy and birth related problems such as diabetes and pregnancy •Many rarer complications such as protozoan infections •Fetal assessment, which is absolutely central to MFM practice •Medico-legal aspects •Sickle cell disease - a major problem for patients of African descent New chapters include: •Recurrent early pregnancy losses •Invasive hemodynamic monitoring •Chronic and acute hypertension •Neurological disorders •Maternal obesity •Assessment of fetal genetic disorders •First and second trimester screening"